2012
DOI: 10.1111/j.1365-2028.2011.01315.x
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal soil infectivity and spores distribution across plantations of tropical, subtropical and exotic tree species: a case study from the forest reserve of Bandia, Senegal

Abstract: plantations. Le nombre et la richesse des spores, de même que le PIM des sols étaient réduits dans les plantations d'arbres. Parallèlement, la quantité de plantes annuelles herbacées conservées hors des plantations d'arbres était plus grande que celle qui poussait sous les arbres plantés. La colonisation était plus forte dans le système radiculaire des plantes herbacées poussant dans la nature que dans celles poussant sous les arbres plantés. Les comparaisons nous permettent de conclure que le type de végétati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Recently this iconic tree is genetically identified as V. pachyceras based on multi-locus plastid gene sequences (Suleiman et al, 2018). Many members of this genus are recognized as species that are useful for re-vegetation of water-stressed and low-nutrient soil environments (Sene et al, 2012b; Sene and Sylla, 2014). V. pachyceras was, however, damaged by the gulf war in 1990 and, the remaining plants patchiness are under the threat of extinction (Kaitharan, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently this iconic tree is genetically identified as V. pachyceras based on multi-locus plastid gene sequences (Suleiman et al, 2018). Many members of this genus are recognized as species that are useful for re-vegetation of water-stressed and low-nutrient soil environments (Sene et al, 2012b; Sene and Sylla, 2014). V. pachyceras was, however, damaged by the gulf war in 1990 and, the remaining plants patchiness are under the threat of extinction (Kaitharan, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, trees in desert regions often represent “fertility islands” for many species (Rodríguez-Zaragoza et al, 2008; Kavamura et al, 2013), which in turn influence long-term vegetation dynamics and ecosystem processes. Moreover, they have a role in combating land degradation through stabilizing soil surfaces by preventing soil erosion and in facilitating plant recruitment and survivorship (El-Sheikh et al, 2010; Sene et al, 2012b, 2013; Kavamura et al, 2013; Sene and Sylla, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, a study conducted in Benin showed an equal distribution between Glomus and Scutellospora species in a woodland of Isoberlina doka (Houngnandan et al, 2009). This AMF diversity described in Benin is low as compared to that found in the reserve of Bandia in Senegal (Sene et al, 2012) and those in the arid and semi-arid areas of Africa and elsewhere (Bâ et al, 1996;Mohammad et al, 2003;Bouamri et al, 2006;Ndoye et al, 2012;Kachkouch et al, 2012). In Senegal, molecular diversity studies of AMF performed on acacia trees showed only the presence of Glomus in their roots, suggesting a preferential mycorrhization of these trees because other genera have been isolated in their rhizosphere (Manga et al, 2007;Ndoye et al, 2012).…”
Section: Introductionmentioning
confidence: 76%
“…The genus Glomus is the most diverse in our study with six species, representing 40% of all the species found in roots of cowpea. The predominance of this genus in most ecosystems like Senegal (Manga et al, 2007;Sene et al, 2012 ;Ndoye et al, 2012), China (Zhao and Zhao, 2007;Wang et al, 2008) Bootstrap support values for branches were estimated from 1.00 replicates. The corresponding accession numbers ranging from KC588975 to KC599000 were given by Genbank.…”
Section: Discussionmentioning
confidence: 99%
“…The results are consistent with a previous report by Onguene and Kuyper (2001), who demonstrated interspecific variability in AMF colonization within the same rainforest site in Cameroon. In Senegal, the positive role of the legume herb Cassia obtusifolia L. in the efficient dispersal of AMF propagules has been demonstrated in both natural and planted forests (Duponnois et al, 2001; Sene et al, 2012; Sene et al, 2012). Results from Zhang et al (2004) in logged and preserved forest areas in the subtropical region of China, and Guadarrama et al (2008) in a secondary dry forest in Oaxaca, Mexico, also suggest that herbaceous plants may be particularly efficient in spreading AMF.…”
Section: Discussionmentioning
confidence: 99%